The current and future role of laboratory medicine for diagnosing gestational diabetes mellitus - Montagnana, Martina; Danese, Elisa; Lippi, Giuseppe (Journal of Laboratory and Precision Medicine, 2019)
Gestational diabetes mellitus (GDM) is currently defined as any degree of glucose intolerance with onset or first recognition during pregnancy. Although this condition is typically diagnosed with evidence of abnormal plasma glucose values after glucose load, there is no international consensus regarding timing of screening and the optimal cut-off points. Some epigenetic alterations, such as DNA methylation and small non-coding RNAs, seem to play a key role in the pathogenesis of disorders of glucose metabolism, and it has also been hypothesized that epigenetic signatures could even find an important place in GDM diagnostics. In a foreseeable future, it is hence conceivable that the assessment of some predictive epigenetic biomarkers may allow early identification of women at enhanced risk of developing pregnancy complications, even before glucose metabolism is significantly impaired. Therefore, this article provides a brief update on screening/diagnostic approaches currently used in clinical practice, an overview of important studies in which epigenetic mechanisms have been associated with the pathogenesis of GDM and, finally, the emerging diagnostic contribution of these epigenetic biomarkers.